The impacts of covid-19 on gender dynamics and power relations among men and women involved in cross border fish trade in Zambia and Malawi - Mudege, Netsayi N.; Mwema, Catherine; Kakwasha, Keagan; Chisopo, Andrew; Manyungwa-Pasani, Chikondi; Banda, Lisungu; Kaunda, E.; Marinda, Pamela (Elsevier, 2022)
This paper explores the impact of the COVID-19 pandemic and the measures to mitigate it on gender dynamics and power relations among men and women involved in cross border fish trade in Zambia and Malawi and the ensuing policy implications to support the fisheries value chain. The paper is based on qualitative and quantitative data collected in Zambia and Malawi in October and November 2021. We conducted quantitative surveys implemented the Cognitive Edge Sensemaker Tool and the Emergency Market Mapping and Analysis toolkit (EMMA to understand the dynamics of cross border fish trade before and during the COVID-19 pandemic. A social relations approach, focusing on gender relations, was used to analyze the data. Findings suggest that women cross-border fish traders are caught up in a complex web of networks and relationships that are disempowering to them. Some measures put in place to mitigate the impact of the COVID-19 pandemic lacked an understanding of the historical perspective and dynamics of women in fish trading communities further marginalizing men and women cross border fish traders. Some measures exacerbated hidden violence against women and overt forms of violence against men. Since most of the violence occur across state boundaries, there is a need for inter-country coordination to ensure that the rights of women and men cross border fish traders are protected. Policy measures could include educating police officers for even-handedness when enforcing COVID-19 rules and providing mechanisms for reporting abusive practices.